PENGARUH JENIS KAYU DAN KOMPOSISI PEREKAT TAHAN CUACA TERHADAP SIFAT PAPAN PARTIKEL DUA JENIS KAYU HUTAN TANAMAN INDUSTRI - Suwandi Kliwon; M I lskandar; Paribotro Sutigno Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
This  paper  deals  with  an experiment   on  the effect of  two  timber  estate  wood  species  i.e. jeungjing  (Albizia.falcataria  Back),  tusam  (Pinus  merkusii Yung  et de  Vries)  and  the  composition   of  weather  resistance  resin  (phenol  formaldehyde)  on the properties  of particle  board.All  wood  samples  were obtained  from  West Java.  The sample  cut  into 2 x 2 cm, 4 x 4 cm and 6 x 6 cm with 5 mm thick, respectively. Wood particles were glued with phenol   formaldehyde resin. Particle  board  were  made  with  3 glue composition  ( 10%, 12%  and  14%)   based on dry  weight of wood particle  and 3 wood particle  dimension   (0.5  mm  x 20 mm x 20 mm,  0.5 mm x 40 mm x 40 mm  and 0.5 mm x 60 mm  x 60 mm).The properties  of particle  board  were  tested  with  Indonesia  Industry  Standard  (SIl.  079783).The  result  indicated that:  The physical  and  mechanical  properties  generally  met  Indonesian  Standard.  Analysis  of variance  for  internal    bond,   shear  strength  and  bending  strength  were significant  different on  wood  species, particle  size and  the portion of  phenol   formaldehyde liquid  resin. The  portion of  14%   phenol   formaldehyde  liquid  resin  based on the  dry  wood  particle,   its physical   and  mechanical   properties   were  best,   compared   with  others portion   of phenol   formaldehyde  liquid resin (10%  and 12%).